Traditional Religious Authorities in New Media: Cariustadz.id Platform as An Alternative Cyber Fatwa and Da’wah Media among the Middle-Class Urban Muslims - Arif Zamhari; Muhamad Ibtissam Han; Zulkifli Zulkifli (AHKAM : Jurnal Ilmu Syariah, 2021)
This study examines the recent developments of religious authorities among middle-class urban Muslims. It is constructed due to the emergence of new religious authorities in Indonesia after the collapse of the New Order and the response of traditional santri involving the use of new media technology. With a phenomenological approach, the study focuses on the Cariustadz.id platform as a Cyber Fatwa and Islamic preaching media developed by Pusat Studi Qur’an/PSQ (Center for Qur’an Studies) to respond to the trending pengajian (sermon) activities among urban Muslims, the majority of whom are transnational groups including Salafi and Jamaah Tabligh. The Cariustadz.id platform has actively played a part in accommodating their aspirations with various facilities and easy access through an information technology-based application (a new media).As a result, the study argues that the moderate Islam discourse offered by the Cariustadz.id platform is not a mainstream but an alternative to religious activities for middle-class urban Muslims. In addition, Cariustadz.id is a new media used for traditional religious authority to compete with new religious authority in religious fatwa and Islamic discourse in Indonesia. This study is significant to show that Cyber Fatwa and Islamic preaching in the form of new media can be used as a counter narrative for traditional religious authorities in dealing with the proliferation of the so called new religious authorities da’wah movement and Salafi and radical preaching movement in new media.Abstrak:Artikel ini mengkaji perkembangan terkini otoritas keagamaan kalangan kelas menengah Muslim perkotaan. Hal ini dilatarbelakangi oleh munculnya otoritas keagamaan baru di Indonesia pasca runtuhnya Orde Baru dan respons santri tradisional yang melibatkan penggunaan teknologi media baru. Dengan pendekatan fenomenologis, penelitian ini berfokus pada platform Cariustadz.id sebagai media fatwa siber dan dakwah Islam alternatif yang dikembangkan oleh PSQ (Pusat Studi Qur’an). Platform itu untuk merespons kegiatan pengajian yang sedang tren di kalangan Muslim perkotaan, yang mayoritas pesertanya adalah kelompok transnasional termasuk Salafi dan Jamaah Tabligh. Cariustadz.id berperan aktif dalam menampung aspirasi mereka dengan berbagai fasilitas dan kemudahan akses melalui aplikasi teknologi informasi.Penelitian ini menunjukkan bahwa wacana Islam mode yang ditawarkan oleh platform Cariustadz.id bukanlah mainstream, melainkan kegiatan keagamaan alternatif bagi Muslim perkotaan kelas menengah. Selain itu, Cariustadz.id merupakan media baru yang digunakan otoritas keagamaan tradisional untuk berkompetisi dengan otoritas keagamaan baru di bidang fatwa keagamaan dan wacana keislaman di Indonesia. Studi ini signifikan menunjukkan bahwa fatwa siber dan dakwah Islam dalam bentuk media baru dapat digunakan sebagai kontranarasi bagi otoritas agama tradisional dalam menghadapi menjamurnya apa yang disebut gerakan dakwah otoritas keagamaan baru dan gerakan dakwah Salafi dan radikal di media baru.